2016
DOI: 10.3389/fmicb.2016.01959
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces and non-Saccharomyces Competition during Microvinification under Different Sugar and Nitrogen Conditions

Abstract: The inoculation of wines with autochthonous yeast allows obtaining complex wines with a peculiar microbial footprint characteristic from a wine region. Mixed inoculation of non-Saccharomyces yeasts and S. cerevisiae is of interest for the wine industry for technological and sensory reasons. However, the interactions between these yeasts are not well understood, especially those regarding the availability of nutrients. The aim of the present study was to analyze the effect of nitrogen and sugar concentration on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 40 publications
8
31
0
Order By: Relevance
“…It is important to note what nitrogen sources are left in the grape must after non-Saccharomyces inoculation and before sequential Saccharomyces addition in order to ensure that the remaining nitrogen is sufficient for S. cerevisiae to complete fermentation as nitrogen consumption profiles of non-Saccharomyces yeasts, for example Hanseniaspora vineae and Metschnikowia pulcherrima have been shown to affect the growth of Saccharomyces yeasts . A study by Lleixà et al (2016) confirmed that nitrogen consumption by non-Saccharomyces yeasts before Saccharomyces inoculation can increase the risk of sluggish or stuck fermentations.…”
Section: Yeast Interactionsmentioning
confidence: 96%
“…It is important to note what nitrogen sources are left in the grape must after non-Saccharomyces inoculation and before sequential Saccharomyces addition in order to ensure that the remaining nitrogen is sufficient for S. cerevisiae to complete fermentation as nitrogen consumption profiles of non-Saccharomyces yeasts, for example Hanseniaspora vineae and Metschnikowia pulcherrima have been shown to affect the growth of Saccharomyces yeasts . A study by Lleixà et al (2016) confirmed that nitrogen consumption by non-Saccharomyces yeasts before Saccharomyces inoculation can increase the risk of sluggish or stuck fermentations.…”
Section: Yeast Interactionsmentioning
confidence: 96%
“…Combination wines made during 2012 and 2013 scored lower in perceived acidity than VIN13 wines (2012 and 2013). However, succinic acid can also contribute to perceived acidity (Taillandier et al, 2014;Lleixá et al, 2016). There were significant differences in the concentration of succinic acid among wines made over the three vintages.…”
Section: Principal Component Analysis (Phenolic Compounds)mentioning
confidence: 99%
“…Some non-Saccharomyces, as well as some non-conventional species of Saccharomyces, present good fermentative capacities and, are able to produce wines with lower levels of ethanol and higher concentrations of glycerol [1]. They are also able to avoid stuck fermentations, as they can grow at lower temperatures [2,3] as well as being nitrogen [4] and salt tolerant [5]. Moreover, mixed inoculations of non-Saccharomyces, S. cerevisiae yeasts, and lactic acid bacteria (LAB) in sequential fermentations are of great interest to the wine industry for various technological and sensorial reasons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mixed inoculations of non-Saccharomyces, S. cerevisiae yeasts, and lactic acid bacteria (LAB) in sequential fermentations are of great interest to the wine industry for various technological and sensorial reasons [6]. In addition, a peculiar microbial footprint that is characteristic of a particular wine region may be imprinted onto a wine if inoculation with autochthonous yeast is performed [3].…”
Section: Introductionmentioning
confidence: 99%